Value proposition: application of value creation activities model in the supermarket (VCAM-S) / Proposição de valor: aplicação do value creation activities model no varejo supermercadista (VCAM-S) - Paulo R. Condi; Dario De O. Lima Filho; Caroline P. S. Finocchio; Filipe Quevedo Silva (RAM. Revista de Administração Mackenzie, 2018)
Purpose: The purpose of this writing is to analyze the activities of the retail supermarket in order to propose value to its clients, describing and associating them in their respective sources of value identified by a Value Creation Activities Model-Supermarket (VCAM-S). Additionally, we seek to identify the words that best represent the meaning of “proposing value” and the product categories of the supermarket that most clients value. Originality/value: The development and implementation of VCAM-S works to identify new value activities in the supermarket. Based on this application, it is intended to suggest activities that enhance the delivery of value to the client. Design/methodology/approach: Bibliographical research and field research were carried out. Twelve retail supermarket specialists were interviewed, including managers, entrepreneurs and consultants with at least eight years of experience in the supermarket sector. Through the qualitative approach, a script of semi-structured interviews with open questions was used. Later, the statements were transcribed and analyzed through the technique of content analysis. Findings: The VCAM-S identified 8 value proposition activities, 71 subactivities and five value sources. It was found that the product categories “FFV”, “Butcher” and “Bakery” were the sections that most proposed value to customers. The words that best represent the meaning of “proposing value” are service, convenience, location, variety and price. The results of the research contribute to the current debate on value and adapt the traditional VCAM to the retail supermarket. The VCAM-S allows for the identification and prospection of value propositions from the perspective of companies, associating them with valuable sources and activities. Objetivo: Analisar as atividades do varejo supermercadista para propor valor ao seu cliente, descrevendo-as e associando-as em suas respectivas fontes de valor identificadas pelo Value Creation Activities Model-Supermarket (VCAM-S). Adicionalmente, busca-se identificar as palavras que melhor representam os significados de propor valor e as seções do supermercado que mais propõem valor aos clientes. Originalidade/relevância: A aplicação do VCAM-S inovou ao identificar novas atividades de valor. Com base nessa aplicação, pretende-se sugerir atividades que potencializem a entrega de valor ao cliente. Principais aspectos metodológicos: Foi realizada uma pesquisa bibliográfica e posteriormente a pesquisa de campo, entrevistando 12 especialistas do varejo supermercadista, entre gerentes, empresários e consultores com experiência mínima de oito anos. Pela abordagem qualitativa, foi utilizado um roteiro de entrevistas semiestruturado com questões abertas; posteriormente, os depoimentos foram transcritos e analisados por meio da técnica de análise de conteúdo. Síntese dos principais resultados: O VCAM-S identificou 8 atividades de proposição de valor, 71 subatividades e 5 fontes de valor. Constatou-se que as seções de “FLV”, “Açougue” e “Padaria” são as seções que mais propõem valor para os clientes e as palavras que melhor representam o significado de propor valor são: atendimento, comodidade, ambiente, estacionamento, localização, variedade e preço. Os resultados da pesquisa contribuem para o debate atual sobre valor e adapta o VCAM tradicional para o varejo supermercadista. O VCAM-S permite a identificação e prospecção das proposições de valor na perspectiva das empresas, associando-as às fontes e atividades de valor.